Exploring the Role of Consumer Trust and Price in Shaping Online Purchasing Decisions: A Case Study of @Dlesend_ Personal Shopping Service - Verlin; Luter Girsang; Purnama Yanti Purba (Yayasan Bina Bisnis Nusantara Medan, 2025)
This research aims to determine the influence of consumer trust and price on purchasing decisions using the online personal shopping service @Dlesend_. The phenomenon of increasing use of personal shopping services on social media, particularly Instagram, indicates a change in consumer behavior when shopping for foreign products without having to travel directly. This research uses a quantitative approach with an associative research design. The population in this study consists of all consumers who have used the @Dlesend_ service, with a sample size of 99 respondents selected through purposive sampling. Data was analyzed using multiple linear regression. The results show that: (1) Consumer trust has a positive and significant effect on purchasing decisions, meaning that the higher the level of consumer trust in transparency, reputation, and transaction security, the higher the tendency to purchase; (2) Price also has a positive and significant effect on purchasing decisions, indicating that a fair and transparent price perception can encourage purchasing decisions; (3) Simultaneously, consumer trust and price significantly influence purchasing decisions using the online personal shopping service @Dlesend_. The coefficient of determination (R²) value of 0.187 indicates that these two variables explain 18.7% of the variation in purchasing decisions, while the remainder is influenced by other factors such as service quality and promotion. This research confirms that trust is the most dominant factor in purchasing decisions in online-based personal shopping services.